Expanding the phenome and variome of skeletal dysplasia. (December 2018) - Maddirevula, Sateesh; Alsahli, Saud; Alhabeeb, Lamees; Patel, Nisha; Alzahrani, Fatema; Shamseldin, Hanan; Anazi, Shams; Ewida, Nour; Alsaif, Hessa; Mohamed, Jawahir; Alazami, Anas; Ibrahim, Niema; et al.
Abstract Purpose To describe our experience with a large cohort (411 patients from 288 families) of various forms of skeletal dysplasia who were molecularly characterized. Methods Detailed phenotyping and next-generation sequencing (panel and exome). Results Our analysis revealed 224 pathogenic/likely pathogenic variants (54 (24%) of which are novel) in 123 genes with established or tentative links to skeletal dysplasia. In addition, we propose 5 genes as candidate disease genes with suggestive biological links (WNT3A, SUCO, RIN1, DIP2C, andPAN2 ). Phenotypically, we note that our cohort spans 36 established phenotypic categories by the International Skeletal Dysplasia Nosology, as well as 18 novel skeletal dysplasia phenotypes that could not be classified under these categories, e.g., the novelC3orf17 -related skeletal dysplasia. We also describe novel phenotypic aspects of well-known disease genes, e.g., PGAP3 -related Toriello–Carey syndrome–like phenotype. We note a strong founder effect for many genes in our cohort, which allowed us to calculate a minimum disease burden for the autosomal recessive forms of skeletal dysplasia in our population (7.16E-04), which is much higher than the global average. Conclusion By expanding the phenotypic, allelic, and locus heterogeneity of skeletal dysplasia in humans, we hope our study will improve the diagnostic rate of patients with these conditions.